Outil d’apprentissage à la gestion des mesures préventives en santé et sécurité du travail basé sur les coûts - Sylvie Gravel; Jessica Dubé; Carole Sylvestre (Perspectives Interdisciplinaires sur le Travail et la Santé)
This article presents the results of a cost-based occupational health and safety (OHS) management learning tool. The project was conducted in two phases : 1) developing, with practicing managers, five cost-focused case studies (n = 5) of work-related accidents or illnesses ; 2) testing the abilities of management students (n = 22) to identify the costs of an event and anticipate the costs of an aggravated situation. After studying three cases, students could easily identify and calculate the direct and indirect costs associated with wages and lost production, but underestimated the costs of employee replacement and OHS management. Likewise, they could easily predict the costs of situations aggravated by union threats. This learning tool could be included in continuing education workshops and mandatory training.